Draft Annual Plan 1984-85 Union Territory of Lakshadweep - Planning Commission (Planning Commission, 1984)
Agriculture in Lakshadweep is confined to Coconut cultivation which is the mainstay of the islanders who are small and marginal farmers having holdings of size below one hectare at an average and who used to adopt unscientific crop culture. Since land is limited any extensive cultivation is impossible. Therefore production has to be increased through scientific methods of cultivation and encouraging inter cultivation and intensive cultivation of suitable crops. Farmers belonging to ST and economically backward, agricultural developments in islands are to be taken up through distribution of fertilisers, seeds, implements etc.
Planning Department